English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

The answer is Yes!

Numerator = 1 + tanx = 1 + (sinx/cosx) = (cosx + sinx)/cosx
Denominator = 1+ cotx = 1+ (cosx/sinx) = (sinx + cosx)/sinx

Then,

(1+tanx) / (1+cotx) = sinx/cosx = tanx.

2006-11-28 10:50:21 · answer #1 · answered by sanjayd_411 2 · 0 0

trick is to unravel the main complicated section that's clearly the left side (a million + tan x)/ (a million+cot x) substitute cot to a million/tan x (a million+ tan x)/ (a million+ (a million/tan X) (a million+ tan X) / ((tan X +a million)/ tan X) ( a million+ tan x) X tan x/ (tan x + a million) cancel out one yet another and you get tan x = tan x

2016-10-13 07:38:07 · answer #2 · answered by thedford 4 · 0 0

(1 + tan(x))/(1 + cot(x))
(1 + tan(x))/(1 + (cosx/sinx))
(1 + (sinx/cosx)) / ((sin(x) + cos(x))/sin(x))
((cos(x) + sin(x))/(cos(x)) / ((sin(x) + cos(x))/sin(x))
((cos(x) + sin(x))/cos(x)) * ((sin(x)/(sin(x) + cos(x)))
(sin(x) * (cos(x) + sin(x))) / (cos(x) * (cos(x) + sin(x))
(sin(x))/(cos(x))
tan(x)

so

(1 + tan(x))/(1 + cot(x)) = tan(x)

2006-11-28 11:56:38 · answer #3 · answered by Sherman81 6 · 0 0

fedest.com, questions and answers